1997
DOI: 10.1111/j.1432-1033.1997.00805.x
|View full text |Cite
|
Sign up to set email alerts
|

Electron Transfer Between Spinach Plastocyanin Mutants and Photosystem 1

Abstract: Two distinct regions of plastocyanin, one hydrophobic and one acidic, are generally thought to be involved in the electron-transfer reactions with its physiological partners, cytochromef and photosystem 1. To probe the importance of the hydrophobic patch in the reaction with photosystem 1, seven mutant plastocyanin proteins have been constructed with the following mutations : Gly7Ala, GlygAsp, Serll Asp, Serl lGly, Pro36Gly, Ser85Thr and Gln88Asn. The electron-transfer reaction was investigated by transient fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 44 publications
2
29
1
Order By: Relevance
“…Control experiments analyzing the interaction of cloned WT diatom Cyt with PSI showed biphasic kinetics for the re-reduction of photooxidized P 700 + by Cyt (not shown), the Cyt concentration dependence of the k OBS for both phases confirming the occurrence of the mechanism previously described for the Phaeodactylum Cyt/PSI couple and other eukaryotic donor/PSI systems [13,17,18,27,[42][43][44]:…”
Section: Kinetic Analysissupporting
confidence: 65%
“…Control experiments analyzing the interaction of cloned WT diatom Cyt with PSI showed biphasic kinetics for the re-reduction of photooxidized P 700 + by Cyt (not shown), the Cyt concentration dependence of the k OBS for both phases confirming the occurrence of the mechanism previously described for the Phaeodactylum Cyt/PSI couple and other eukaryotic donor/PSI systems [13,17,18,27,[42][43][44]:…”
Section: Kinetic Analysissupporting
confidence: 65%
“…When looking at the protein as it is commonly depicted in the literature, the redox site at the ''northern pole'' of the molecule is in the vicinity of the ''hydrophobic'' interaction patch and ''west'' of the negatively charged interaction patch [25]. Site-directed mutagenesis has been recently used to modify both the copper ligation and interaction patches [26]. In this work, a site-specifically engineered disulphide bridge, located in a region of the poplar plastocyanin structure opposite to the copper active site, was introduced [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…The previously reported mutational analyses, cross-linking studies, and ion strength dependencies of the Pc-PSI and Pc-cyt b 6 f electron transport rates have shown that the acidic patch residues of Pc and the basic residues of PSI and cyt b 6 f are responsible for the Pc-PSI (Hippler et al, 1989(Hippler et al, , 1997Lee et al, 1995;Sigfridsson et al, 1996Sigfridsson et al, , 1997Young et al, 1997) and Pc-cyt b 6 f electron transport reactions (Modi et al, 1992b;Lee et al, 1995;Hippler et al, 1998;Gong et al, 2000b;Illerhaus et al, 2000). Therefore, the acidic patch of Pc may increase its local concentration around PSI and cyt b 6 f, thus facilitating the rapid formation of the electron transfer complex by occasionally forming dynamic salt bridges (Bergkvist et al, 2001) or long-distance ion pairs (Figure 7, left).…”
Section: Roles Of the Acidic And Hydrophobic Residues Of Pc In The Pcmentioning
confidence: 99%
“…Mutational analyses of Pc revealed that the residues in the hydrophobic patch that surrounds the copper ion, such as Leu-12 and Ala-90 (see Supplemental Figure 1 online), and those in the acidic patch located adjacent to the hydrophobic patch, such as and Asp-61 of spinach (Spinacia oleracea) Pc (see Supplemental Figure 1 online), are reportedly important for Pc-PSI (Haehnel et al, 1994;Lee et al, 1995;Hippler et al, 1996;Sigfridsson et al, 1996Sigfridsson et al, , 1997Young et al, 1997) and Pc-cyt b 6 f (Modi et al, 1992b;Lee et al, 1995;Sigfridsson, 1998;Hope, 2000;Illerhaus et al, 2000) electron transport in eukaryotic plants. Mutational and cross-linking studies of the PSI from C. reinhardtii revealed that two Trp residues close to P700 stemming from the PsaA and PsaB subunits, PsaA-Trp-651 and PsaB-Trp-627 in Chlamydomonas reinhardtii (Sommer et al, 2002(Sommer et al, , 2004, and clusters of basic residues located adjacent to the Trp residues from the PsaF subunit, PsaF-Lys-16, PsaF-Lys-23, and PsaF-Lys-30 in C. reinhardtii (Hippler et al, 1989(Hippler et al, , 1997(Hippler et al, , 1998, participate in the electron transport (Busch and Hippler, 2011).…”
Section: Introductionmentioning
confidence: 99%